2012
DOI: 10.1111/j.1460-9568.2012.08263.x
|View full text |Cite
|
Sign up to set email alerts
|

Opposite effects of ketamine and deep brain stimulation on rat thalamocortical information processing

Abstract: Opposite effects of ketamine and deep brain stimulation on rat thalamocortical information processing Sofya P Kulikova (1,2)*, Elena A Tolmacheva (1,2)**, Paul Anderson (1,2,3), Julien Gaudias (1,2)***, Brendan E Adams (1,2)****, Thomas Zheng (1,2,3), and Didier Pinault (1,2)(1) INSERM U666, physiopathologie et psychopathologie cognitive de la schizophrénie, Strasbourg, France. Abstract:Sensory and cognitive deficits are common in schizophrenia. They are associated with abnormal brain rhythms, including distu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
62
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 85 publications
11
62
0
Order By: Relevance
“…Full data are shown in Supplementary Table S2A-D. of information received by the PFC, by the promotion of an abnormally increased functional connectivity of this neural subsystem. This suggested mechanism is not only consistent with recent human brain imaging data showing that subanesthetic ketamine treatment increases global brain functional connectivity (Driesen et al, 2013), but is also consistent with emerging electophysiological data supporting a reduced signal-to-noise after ketamine treatment in the hippocampal CA3 subfield (Saunders et al, 2011) and of gamma oscillations in the somatosensory thalamocortical system (Kulikova et al, 2012) of rodents. Our data suggest that similar mechanisms may occur in the PFC, where ketamine is known to directly increase the amplitude of gamma oscillations through the blockade of local NMDA receptors (McNally et al, 2011) and where the NMDA receptor antagonist MK-801 has been shown to disrupt the firing pattern of PFC neurons (Jackson et al, 2004).…”
Section: Discussionsupporting
confidence: 76%
“…Full data are shown in Supplementary Table S2A-D. of information received by the PFC, by the promotion of an abnormally increased functional connectivity of this neural subsystem. This suggested mechanism is not only consistent with recent human brain imaging data showing that subanesthetic ketamine treatment increases global brain functional connectivity (Driesen et al, 2013), but is also consistent with emerging electophysiological data supporting a reduced signal-to-noise after ketamine treatment in the hippocampal CA3 subfield (Saunders et al, 2011) and of gamma oscillations in the somatosensory thalamocortical system (Kulikova et al, 2012) of rodents. Our data suggest that similar mechanisms may occur in the PFC, where ketamine is known to directly increase the amplitude of gamma oscillations through the blockade of local NMDA receptors (McNally et al, 2011) and where the NMDA receptor antagonist MK-801 has been shown to disrupt the firing pattern of PFC neurons (Jackson et al, 2004).…”
Section: Discussionsupporting
confidence: 76%
“…Since genetic ablation of NMDARs selectively from PV neurons in awake mice also results in increased baseline power (Korotkova et al, 2010; Carlén et al, 2012), this finding is most likely due to NMDAR hypofunction in PV neurons. Similar results were also obtained from GluN1 hypomorph mice (Dzirasa et al, 2009; Gandal et al, 2012b) and from the acute administration of NMDAR antagonists (phencyclidine, ketamine, or MK-801) to rodents (Leung, 1985; Ma and Leung, 2000, 2007; Pinault, 2008; Ehrlichman et al, 2009; Hakami et al, 2009; Páleníček et al, 2011; Kulikova et al, 2012; Wood et al, 2012; Caixeta et al, 2013; Molina et al, 2014), to humans (Maksimow et al, 2006; Hong et al, 2010), and in in vitro slice preparation (McNally et al, 2011). The most likely mechanistic explanation for these effects is that cortical disinhibition elicited by NMDAR deletion from local PV neurons render the cortical glutamatergic neurons hyper-excitable (Olney and Farber, 1995; Homayoun and Moghaddam, 2007; Lisman et al, 2008; Nakazawa et al, 2012).…”
Section: Discussionsupporting
confidence: 64%
“…Increased baseline gamma oscillations have been reported in patients during psychotic episodes, including visual and auditory hallucinations (Baldeweg et al, 1998; Ropohl et al, 2004; Lee et al, 2006; Becker et al, 2009). Other studies suggest a link between baseline gamma oscillations and negative symptoms (Suazo et al, 2012), working memory (Winterer et al, 2004; Suazo et al, 2012), or synaptic plasticity (Bikbaev et al, 2008; Kulikova et al, 2012). A recent meta-analysis of functional neuroimaging in schizophrenia patients with auditory hallucinations revealed “paradoxical” engagement of A1 cortex, such that left A1 cortex displayed increased activation in the absence of external auditory stimuli (but with auditory verbal hallucinations), and decreased activation when an external stimulus was actually present (Kompus et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, our results demonstrated the following: (1) the suppression of glutamatergic excitatory neurotransmission with glutamate release inhibitors attenuated the MK-801-increased cortical GBO power; (2) the potentiation of GABAergic inhibitory neurotransmission through the a2/ The blockade of NMDAr by MK-801 may activate both PN and FS/PV-IN in the above local circuits through the disinhibition of PN, resulting in an increase in basal GBO power. Moreover, given reports that a perfusion of MK-801 or ketamine increased the power of in vitro GBO in the PFC slices (McNally et al, 2011) and a local application of MK-801 or ketamine on the cortical surface increased GBO power of the local field potential in the cortex (Kulikova et al, 2012), the action site of MK-801 increasing GBO power in the present study might be present in cortical local circuits.…”
Section: Discussionmentioning
confidence: 79%